Evaluation of hemodynamic effects of xenon in dogs undergoing hemorrhagic shock (Clinics, 2013)
OBJECTIVES: The anesthetic gas xenon is reported to preserve hemodynamic stability during general anesthesia. However, the effects of the gas during shock are unclear. The objective of this study was to evaluate the effect of Xe on hemodynamic stability and tissue perfusion in a canine model of hemorrhagic shock. METHOD: Twenty-six dogs, mechanically ventilated with a fraction of inspired oxygen of 21% and anesthetized with etomidate and vecuronium, were randomized into Xenon (Xe; n = 13) or Control (C; n = 13) groups. Following hemodynamic monitoring, a pressure-driven shock was induced to reach an arterial pressure of 40 mmHg. Hemodynamic data and blood samples were collected prior to bleeding, immediately after bleeding and 5, 20 and 40 minutes following shock. The Xe group was treated with 79% Xe diluted in ambient air, inhaled for 20 minutes after shock. RESULT: The mean bleeding volume was 44 mL.kg-1 in the C group and 40 mL.kg-1 in the Xe group. Hemorrhage promoted a decrease in both the cardiac index (p